RODA LANGKAH CITA-CITAKU (ROLACIKU): TO OVERCOME MONOTONOUS LEARNING PUBLIC SPEAKING - Khumairo, Dahlia; Asya’adah, Asya’adah; Yanti, Lismei Sinti; P, Anindhita D; Mirza, M. Saiful (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The monotonous learning is a problem in the learning process, actually in public speaking learning will be very boring because it has a regular, repeated pattern with never change, so Roda Langkah Cita-citaku is alternative learning media to overcome monotonous learning public speaking. The aims of this research to overcome public speaking skill by using visual learning of Roda Langkah Cita-citaku student in Rumah Bibit Wajak Malang. The method research is Research and Development (R&D) that oriented in the educational field. The techniques of data collection through explorative studies to review, investigate, and collect information. In this step includes activities such as necessary analysis, literature review, classroom observation, identification of problems in the learning, and also compiles data on supporting and inhibiting factors in learning. Instrument data collection used in the form of suggestion and comments and questionnaire. Data analysis technique that uses the qualitative and quantitative approach. The subject of research is three student in 4th grade. From the three sample are tested, all of the students have different skill. The first Student an excellent speaking skill, second student have the intermediate speaking skill, and the last student has basic speaking skill. The research result showed that learning media of Rolaciku can awaken student motivation to improve their public speaking skill and got a good qualification from the material expert and design expert, based on the validation result stated that 84.44% from material experts and 82.85% from a media expert.